A review on Online Vs Offline Marketing: The future of retailing in India - Sant, Tatavarty Guru (International Journal of Psychosocial Rehabilitation, 2020)
Nowadays, online retail sector is seeking interest over the traditional retail business in India. The momentum of online retail business has gained so much pace that it is hampering the conventional retail business market. Luckily, more and more business deals are been provided online with better prices leading to the attention of larger population. While the online merchants have reported a record-breaking growth and is on track to keep expanding fast, the conventional retail merchants were observed to have struggling business with reduced annual sales. Moreover, stimulated by the swift growth of our financial system, the whole of retail market is not only set to develop very rapidly but both organized retail and online retail jointly characterize an insignificant 7.5% of the calculated total retail market in the country. Therefore, in this paper an attempt is made to have an insight about online vs offline channel and future of retailing in India.